2008
DOI: 10.1093/jmedent/45.6.1080
|View full text |Cite
|
Sign up to set email alerts
|

Repellency of Hydrogenated Catmint Oil Formulations to Black Flies and Mosquitoes in the Field

Abstract: The essential oil of catmint, Nepeta cataria L., was hydrogenated to yield an oil enriched in dihydronepetalactone (DHN) diastereomers, termed. This material was used for the preparation of liquid alcohol-based and lotion formulations. The efficacy of these formulations as repellents was tested after application to human test subjects at two locations in the United States: Maine and Florida. In Maine, data on repellency of the hydrogenated catmint oil formulations toward black flies (Simulium decorum Walker) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The results of the evaluation in Florida showed that all formulations led to protection for more than 4 h from a mixed population of mosquitoes. The 15 wt% lotion conferred complete protection from bites for more than 6 h.[62]…”
Section: Insect Repellent Activitymentioning
confidence: 99%
“…The results of the evaluation in Florida showed that all formulations led to protection for more than 4 h from a mixed population of mosquitoes. The 15 wt% lotion conferred complete protection from bites for more than 6 h.[62]…”
Section: Insect Repellent Activitymentioning
confidence: 99%
“…The plant based repellents may have good role in reducing the biting nuisance and infections by preventing the man-fly contact (Curtis 1992; Fradin 1998; Fradin and Day 2002; Usip et al 2006; Spero et al 2008) and to preclude any adverse effect that could emanate from the use of synthetic repellents (Osimitz et al 1995; Goodyer and Behrens 1998). Many plants oils and material have been tested as potential insect repellents (King 1954; Quarles 1996; Tawatsin et al 2001) and are available in the market either in single or in combination with other.…”
Section: Discussionmentioning
confidence: 99%
“…The hydrogenated oil is enriched in the repellent, dihyronepatalacetone. Both oils have been shown to be effective against biting insects (Spero et al 2008). They were supplied by E.I.…”
Section: Methodsmentioning
confidence: 99%
“…Members of the catmint genus Nepeta in the family Laminaceae produce essential oils that are effective repellents of mosquitoes. A commercially-available oil from the catmint plant Nepata cataria L. (Lamiales: Lamiaceae) and the hydrogenated catnip oil applied at 15% active ingredient by weight gave 4 to 7 hours of protection from the blackfly Simulium decorum and mosquitoes from the genus Aedes (Spero et al 2008). This new product has not been evaluated for activity against stored-product insects.…”
Section: Introductionmentioning
confidence: 99%